Characterization of knowledge sharing and collaboration practices in a portuguese university: an empirical study - Chedid, Marcello (2019)
The mission of the university is closely related with knowledge management, where there are some key elements that facilitate this management, such as experience in the creation and development of knowledge and an organizational structure that tends to be horizontal. However, some studies indicate difficulties in establishing an organizational culture that focuses on knowledge management with contributions to the collaboration and knowledge sharing (Howell & Annansingh, 2013). According to Tian, Nakamori and Wierzbicki (2009), the universities evidence an individualistic culture where knowledge is related to the experience and the competence of each researcher and/or teacher. In this context, knowledge is frequently considered as property and as a differentiation factor of each individual. Consequently, the individual characteristics tend to show a major impact on knowledge sharing, which, according to some authors, is superior to that caused by the departmental and institutional characteristics (Geuna & Muscio, 2009). Despite many studies focused on knowledge sharing in organizations, the literature shows a limited number of empirical works on the subject in the universities context (Fullwood, Rowley, & Delbridge, 2013), concentrating some of them on institutions from Asian countries (Tohidinia & Mosakhani, 2010). Given that knowledge sharing is a behavior of individual initiative (Bock & Kim, 2001), and that teachers and researchers are key elements in the process of creating and sharing knowledge in the university, this study aims to analyze the behavior of the academic and scientific members of a Portuguese university related to the referred process. This study was conducted on the basis of a questionnaire prepared taking into account the literature on the area. The sample consisted of teachers and researchers from a Portuguese university and the questionnaire was provided online. The data was collected anonymously and analyzed with the statistical software SPSS IBM 24. The results of this work present relevant facts related to the knowledge sharing in the context of the university where the study was conducted. Today, universities are under intense pressure, motivated by the knowledge society and by the internationalization of institutions, where creativity, innovation and entrepreneurship emerge as essential elements of competition. This pressure, on the other hand, demands a positive attitude towards knowledge sharing from the universities in general and from their actors in particular. However, the analysis of the results obtained shows that in general, actions of knowledge sharing occur in an isolated way and concentrated in the internal environment of the institution. Therefore, it is important to establish mechanisms that promote and encourage the sharing of knowledge and, consequently, collaborative relationships.